Utilizing MATLAB computing package as a conceptual tool for solving algebraic problems - Kwelle, Clifford Obioma; Charles-Ogan, Gladys Ibibo (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
MATLAB is a high-level computer language and interactive environment used for numerical computation, technical data analysis, programming, simulation, and visualization. It allows matrix manipulations, function plotting, and solving various equations like quadratic, linear, and simultaneous equations. The paper explains how to solve algebraic problems in mathematics using MATLAB. The aim is to demonstrate that MATLAB is user-friendly, and suitable not only for higher institution students but also for secondary school students, making it easy to handle algebraic problems at the secondary school level. Inbuilt commands are used with simple syntax to manage algebraic processes effectively.